2014
DOI: 10.3126/jnps.v34i1.9165
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcium Levels in Preterm and Term Neonates on Phototherapy

Abstract: Introduction: In addition to known causes of hypocalcemia like, prematurity, Intrauterine growth retardation (IUGR), asphyxia, sepsis, infants of diabetic mothers (IDM), high phosphate formula, Magnesium deficiency, effect of phototherapy on serum calcium levels has caught attention of researchers from time to time. The objectives of this study were to evaluate serum calcium levels in relation to duration of phototherapy, single surface Vs double surface phototherapy in term and preterm neonates. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 4 publications
4
9
1
Order By: Relevance
“…We took a cut value of serum calcium of <7mg/dl. which is similar to cut of value taken by Arora et al [9], karamifer el al [10], Taheri et al [11]. Our study variables are comparable to karamifer el al, Taheri et al, Therani et al, Egbalian et al [7] and Kumar et al [12].…”
Section: Discussionsupporting
confidence: 91%
“…We took a cut value of serum calcium of <7mg/dl. which is similar to cut of value taken by Arora et al [9], karamifer el al [10], Taheri et al [11]. Our study variables are comparable to karamifer el al, Taheri et al, Therani et al, Egbalian et al [7] and Kumar et al [12].…”
Section: Discussionsupporting
confidence: 91%
“…Table no. 3 shows that in the present study jitteriness was observed in 33% of preterm and lethargy was observed in 16.67% of preterm and in the present jitteriness was observed in 11% of term neonates and lethargy was observed in10% of term neonates study after 48 hrs of phototherapy which is comparable to the study done by Arora et al (2014) [14]. This is suggestive that Jssssssitteriness and lethargy is main symptoms in phototherapy induce hypocalcemic newborns.…”
Section: Discussionsupporting
confidence: 81%
“…An earlier study showed a higher incidence of symptomatic hypocalcemia in preterm neonates mainly jitteriness and irritability 10 . Similarly another study recently reported a higher incidence of jitteriness and irritability in preterm neonates subjected to phototherapy 14 . We too have observed similar results among preterm neonates in our study though none of the neonates developed apnoea or convulsions.…”
Section: Discussionmentioning
confidence: 62%